Hey Good Looking, How Have You Been Cooking? The Role of Cooking Method on Cooked Color and Palatability of Beef Steaks - Greta E. Huber (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: This study aimed to determine the palatability and appearance differences between six cooking methods and two degrees of doneness (DOD). Study Description: Strip steaks were cooked using one of six cooking methods (sous vide, oven, grill, flat-top, clamshell, or air fryer) and to one of two DOD: medium rare (145°F) or well done (170°F). Consumers evaluated six samples using a 100-point line scale for juiciness, tenderness, flavor, overall liking, and overall appearance. Acceptability (acceptable/unacceptable) was determined for each trait. Consumers were asked about the visual expectations by determining (yes/no) if the steak’s appearance matched the expected DOD. The Bottom Line: Cooking method influenced appearance ratings and visual expectations of DOD, suggesting that despite similar endpoint temperatures, differences in internal and external color influenced consumer perception and acceptability.
Keywords: cooking method; degree of doneness; consumer